Identifying concept from English translated Quran - Rohana, Ismail; Nurazzah, Abd Rahman; Zainab, Abu Bakar (2017)
Ontology learning is a field of extracting ontological elements to form ontology. Identification of concepts is the main activities within ontology learning. Diverse methods can be used to find concepts. One of the methods is using collocation learning technique. The technique used statistical scores which to test the strength of the connection between terms. In English translated Quran, single term Allah has occurred more frequently. The highest occurrences make the term Allah as concept but ignore the multi terms that related terms to Allah. This paper proposed a method to extract concept. It is based on collocation of terms related to Allah. The collocation used Ngram method. The result shows that the collocation method is able to identify terms related to Allah to be as concepts.